Aktualisasi Nilai-Nilai Pancasila dalam Upaya Membangun Karakter pada Siswa-Siswi di Sekolah Dasar Plus Al-Ghifari - Safitri Nuraini; Fadia Syaira Nur Ambia; Lina Nuraeni Rahmawati; Asifa Nurul Fadilla; Siti Nur Khasanah; Falah Haikal Abdillah; Yasa Revaldi; Dhafin Al Ibrahim; Citra Khoirunnisa; Andri Setiawan; Dian Herdiana; Cecep Ali Jamal (Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effectiveness and implementation of Pancasila values, particularly Belief in the One Almighty God and Just and Civilized Humanity, which were actualized through a short (one-day) intervention program for students at Al-Ghifari Elementary School. This study is based on a community service program implemented over a limited period. The method used is descriptive qualitative, focusing on pre- and post-evaluation of the one-day activity. Data were collected through direct observation during the program implementation and reflections from educators. The results of this short activity indicate that the values of Belief in the One Almighty God were internalized through interactive education sessions based on religion and tolerance. Meanwhile, the values of Humanity were actualized through educational game simulations that emphasize the importance of honesty, justice, and empathy among students. Despite the short (one-day) program, there was an increase in students' enthusiasm and initial understanding of these values, which are important foundations for character building.